A108. Pathophysiology in Diffuse Parenchymal Lung Diseases 2019
DOI: 10.1164/ajrccm-conference.2019.199.1_meetingabstracts.a2577
|View full text |Cite
|
Sign up to set email alerts
|

BBT-877, a Potent Autotaxin Inhibitor in Clinical Development to Treat Idiopathic Pulmonary Fibrosis

Abstract: RATIONALE Idiopathic Pulmonary Fibrosis (IPF) is a progressive, irreversible and fatal lung disease. Its risk factors include age, genetic and environmental/occupational factors. Currently available therapies only slow down disease progression. Autotaxin (ATX) is an extracellular enzyme involved in the hydrolysis of lysophosphatidylcholine (LPC) to form lysophosphatidic acid (LPA). The ATX-LPA-LPA receptor (LPAR) axis has been suggested to play a pivotal role in the pathogenesis and the progression of IPF. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In humans, GLPG1690 was reported to be well tolerated in a phase 1 randomized clinical trial (NCT02179502), safe and efficacious in a phase 2a randomized placebo-controlled clinical trial (NCT02738801), supporting ATX inhibition as a novel treatment for IPF ( 136 , 137 ). In addition, administration of BBT-877, another orally available small molecule inhibitor targeting ATX (IC50 ~6.7 nM), to healthy volunteers in a phase I clinical trial (NCT03830125), did not reveal severe adverse events ( 138 , 139 ). However, the GLPG1690 phase III clinical trial was recently discontinued on account of “low benefit to risk ratio“.…”
Section: Pharmacologic Targeting Of Atx As An Additional Therapeutic Option In Covid-19mentioning
confidence: 99%
“…In humans, GLPG1690 was reported to be well tolerated in a phase 1 randomized clinical trial (NCT02179502), safe and efficacious in a phase 2a randomized placebo-controlled clinical trial (NCT02738801), supporting ATX inhibition as a novel treatment for IPF ( 136 , 137 ). In addition, administration of BBT-877, another orally available small molecule inhibitor targeting ATX (IC50 ~6.7 nM), to healthy volunteers in a phase I clinical trial (NCT03830125), did not reveal severe adverse events ( 138 , 139 ). However, the GLPG1690 phase III clinical trial was recently discontinued on account of “low benefit to risk ratio“.…”
Section: Pharmacologic Targeting Of Atx As An Additional Therapeutic Option In Covid-19mentioning
confidence: 99%
“…BBT-877 is an orally available small molecule inhibitor of ATX that mimics LPA receptor antagonism, leading to the suppression of fibrosis in lung tissue [ 24 , 29 ]. Our current data reveal that BBT-877 administration similarly attenuates kidney hyperfiltration and kidney dysfunction in diabetic states, as revealed by the reduced water intake, urination, and ACR compared to the STZ-vehicle group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor signaling, oxidative stress, and proinflammatory cytokines (such as IL-1β, TNF-α, and IL-6) can stimulate the transcription of TGF-β isoforms in fibrotic tissues [ 15 , 43 , 44 ]. Recently, Lee et al showed that BBT-877 attenuated fibrosis in a mouse model of bleomycin-induced pulmonary fibrosis [ 24 ]. Consistently, our data also showed that TGF-β expression was significantly increased with the expression levels of fibrotic factors, including fibronectin, CTGF, and COL1A1 in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations